The Balance Between Judicial Process Efficiency And Justice In The Implementation Of Plea Bargaining In The National Criminal Code (KUHP) - Hendra; Tri Nugroho Akbar; M. Martindo Merta (Justice Law Review, 2026)
The implementation of plea bargaining in Indonesia's criminal justice system, although offering efficiency in resolving cases, must be carried out with caution to ensure a balance between the efficiency of the judicial process and fairness for the defendant. This mechanism, which is included in Article 199 of the Draft Criminal Procedure Code (RKUHAP), aims to expedite the judicial process by allowing case resolution through an agreement between the public prosecutor and the defendant. However, the main challenge in its implementation is ensuring that plea bargaining does not sacrifice the defendant's rights, especially in cases involving serious crimes. Therefore, while this mechanism can reduce case backlogs and speed up legal processes, it is crucial to maintain transparency, protect human rights, and prevent system abuse. Clear regulations in the RKUHAP and strict supervision from the judiciary and society are essential to ensure that the application of plea bargaining aligns with the principles of substantive justice, without infringing on the defendant's rights.